Desiminasi Model Pembelajaran Multukultural Bermuatan Peristiwa Sejarah Bagi MGMP Sejarah Kabupaten Lampung Selatan - Sumargono; Risma Margaretha Sinaga; Rinaldo Adi Pratama Pratama; Bahtiar Afwan; Navil Alfarisi Abbas; Marzius Insani (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2026)
This community service activity aims to improve the competence of MGMP history teachers in South Lampung Regency in implementing the Multicultural Learning Model with Historical Events. The implementation method includes workshops, group discussions, learning simulations, and evaluation with test instruments and assessment of teaching tool products. In the preparation stage, pre-service observations, literature reviews, partner needs analysis, and coordination with MGMP management were carried out. The training stage is focused on delivering conceptual material on multicultural education and historical empathy, the practice of preparing teaching modules based on historical events, and the application of participatory and reflective learning strategies. Furthermore, the evaluation stage is carried out to measure the improvement of teachers' knowledge, skills, and creativity in designing and implementing multicultural learning. The results of the evaluation showed a significant increase, with an average pre-test score of 69.2 and post test of 85.8, an increase of 16.4%. This achievement proves that the service program is effective in strengthening teachers' understanding of multicultural concepts, improving pedagogical skills, and encouraging the formation of more interactive, inclusive, and contextual history learning practices in accordance with the direction of the Independent Curriculum.